Fiscal Policy : Issues During the Transition in Russia - Alexashenko, Sergei; Lopez-Claros, Augusto (Washington, D.C. : International Monetary Fund, 1998)
Since 1992, the Russian Federation has moved away from a command economy and has laid the foundation of a market-based system. This paper examines some of the key fiscal policy issues that arose in 1992-96, the period following the onset of economic liberalization and reform.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet